Bevacizumab and temozolomide in patients with first recurrence of WHO grade II and III glioma, without 1p/19q co-deletion (TAVAREC): a randomised controlled phase 2 EORTC trial. Issue 9 (September 2018) - van den Bent, Martin J; Klein, Martin; Smits, Marion; Reijneveld, Jaap C; French, Pim J; Clement, Paul; de Vos, Filip Y F; Wick, Antje; Mulholland, Paul J; Taphoorn, Martin J B; Lewis, Joanne; Weller, Michael; et al.
Summary: Background: Bevacizumab is frequently used in the treatment of recurrent WHO grade II and III glioma, but without supporting evidence from randomised trials. Therefore, we assessed the use of bevacizumab in patients with first recurrence of grade II or III glioma who did not have 1p/19q co-deletion. Methods: The TAVAREC trial was a randomised, open-label phase 2 trial done at 32 centres across Europe in patients with locally diagnosed grade II or III glioma without 1p/19q co-deletion, with a first and contrast-enhancing recurrence after initial radiotherapy or chemotherapy, or both. Previous chemotherapy must have been stopped at least 6 months before enrolment and radiotherapy must have been stopped at least 3 months before enrolment. Random group assignment was done electronically through the European Organisation for Research and Treatment of Cancer web-based system, stratified by a minimisation procedure using institution, initial histology (WHO grade II vs III), WHO performance status (0 or 1 vs 2), and previous treatment (radiotherapy, chemotherapy, or both). Patients were assigned to receive either temozolomide (150–200 mg/m 2, orally) monotherapy on days 1–5 every 4 weeks for a maximum of 12 cycles, or the same temozolomide regimen in combination with bevacizumab (10 mg/kg, intravenously) every 2 weeks until progression. The primary endpoint was overall survival at 12 months in the per-protocol population. Safety analyses were done in all patients who started their allocated treatment. The study is registered at EudraCT (2009–017422–39) andClinicalTrials.gov (NCT01164189 ), and is complete. Findings: Between Feb 8, 2011, and July 31, 2015, 155 patients were enrolled and randomly assigned to receive either monotherapy (n=77) or combination therapy (n=78). Overall survival in the per-protocol population at 12 months was achieved by 44 (61% [80% CI 53–69]) of 72 patients in the temozolomide group and 38 (55% [47–69]) of 69 in the combination group. The most frequent toxicity was haematological: 17 (23%) of 75 patients in the monotherapy group and 25 (33%) of 76 in the combination group developed grade 3 or 4 haematological toxicity. Other than haematological toxicities, the most common adverse events were nervous system disorders (59 [79%] of 75 patients in the monotherapy group vs 65 [86%] of 76 in the combination group), fatigue (53 [70%] vs 61 [80%]), and nausea (39 [52%] vs 43 [56%]). Infections were more frequently reported in the combination group (29 [38%] of 76 patients) than in the monotherapy group (17 [23%] of 75). One treatment-related death was reported in the combination group (infection after intratumoral haemorrhage during a treatment-related grade 4 thrombocytopenia). Interpretation: We found no evidence of improved overall survival with bevacizumab and temozolomide combination treatment versus temozolomide monotherapy. The findings from this study provide no support for further phase 3 studies on the role of bevacizumab in this disease. Funding: Roche Pharmaceuticals.